1970-1990 yılları arasında Sovyetler Birliği'nde Türkoloji çalışmalarında "Sovetskaya Türkologiya" dergisi örneği - Kankavi, Janetta (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Türk Dili ve Edebiyatı Anabilim Dalı, 2014)
Bu çalışmanın konusu Sovyetler Birliği'nde 1970-1990 yılları arasında yapılan Türkoloji araştırmalarıdır. Türkoloji ile ilgili materyaller Rus kaynaklarına göre seçilmiş ve "Sovetskaya Türkologiya'' dergisi bu çalışmanın en önemli kaynağı olmuştur. Bu dergide Rus ve Sovyet Türkologlarının Türk Dilbilimi alanında gerçekleşen çalışmaları yer almaktadır. Türkoloji araştırmaları Türk Dilleri, Gramer, Fonetik, Morfoloji, Sentaks, Leksikoloji ve Leksikografya, Diyalektoloji ve Diyalektografya, Eski Türk Yazılı Metinler ve farklı dil konuları üzerinde gerçekleştirilmiştir. "Sovetskaya Türkologiya'' dergisi sadece Rus ve Sovyet Türkologların çalışmalarını değil yabancı Türkologların çalışmalarını da bir araya getirmektedir. Anahtar Kelimeler: Türkoloji gelişimi , Rus ve Sovyet Türkologları , Türk Dilleri , Türk Edebi Dili , Türk Dili Tarihi , Bilimsel Türkoloji araştırmaları .

The subject matter of this study is connected with Turcology researches in the Soviet Union between 1970-1990. The materials on Turcology researches were taken from Russian sources and the "Soviet Turcology'' journal is the main source of this study. This journal includes The Russian and Soviet Turcologists' scientific investigations and their comments on the different spheres of the linguistics. Turcology researches focus on Turkic languages in terms of grammar, phonetics, morphology, syntax, lexicology and lexicography, dialectology and dialectography, earliest Turkic Inscriptions and different aspects of Turcology. "Soviet Turcology'' journal does not only cover Russian and Soviet Turcologists' researches but the articles of foreign scientists as well. Key words: Turcology Development , Russian and Soviet Turc ologists , Turkic Languages, Turkish Literature , History of the Turkic Language , Scientific Turcology Researches .
Turcology researches in the Soviet Union between 1970-1990 "Soviet Turcology" journal, an example
Keywords: Türk Dili ve Edebiyatı; Turkish Language and Literature